A Novel PTCH1 Frameshift Mutation Leading to First Case of Gorlin-Goltz Syndrome with Bilateral Pneumothorax - Aydin, Suphi; Dumanl?, Ahmet; Onrat, Serap Tutgun; Oz, Gurhan; Balci, Aydin; Gencer, Adem; Kilicgun, Haci Ali (Archives of Clinical and Biomedical Research, 2021)
Objective: Gorlin-Goltz syndrome is a rare autosomal dominant inherited syndrome, also known as “basal cell nevus syndrome’’. This rare disorder is caused by mutation in the patched tumor suppressor gene PTCH and located in chromosome 9q22.3q31, which functions as a component of the Hedgehog signaling pathway. It is characterized by multiple basal cell carcinomas, jaw keratocysts, falx cerebri calcification and skeletal anomalies. The syndrome was first described by Gorlin and Goltz in 1960, and has a wide clinical spectrum including ophthalmological, neurological, endocrine and genital pathologies, internal malignancies and mental retardation. Methods: A 22-year-old male patient presented with a left-side spontaneous pneumothorax. After tube thoracostomy, prolonged air leak developed, and computed tomography was performed because of bullous lung. A patient with Gorlin-Goltz syndrome who developed spontaneous pneumothorax in the contralateral lung during clinical follow-up and underwent surgery is presented. The treatment and follow-up of this case are discussed in the light of literature. Results: The NGS analysis results were compatible with the diagnosis of NBCCS (Gorlin-Goltz), and a novel heterozygous frameshift mutation c.1659delC(pS554Afs*11) (pSer554Alafs Ter11) in the PTCH1 gene causing a premature stop codon. The case was evaluated as pathogenic with high probability according to ACMG criteria. Conclusion: This case report; describes for the first time a patient with NBCCS or Gorlin-Goltz Syndrome with basal cell carcinoma caused by a heterozygous frameshift mutation in exon 10 of the PTCH1 gene and was considered highly likely pathogenic according to the ACMG criteria. Therefore, our case; it is important because it is the first presented frameschift mutation in the world, which belongs to Gorlin-Goltz Syndrome.